On love : in the Muslim tradition - Mahmutćehajić, Rusmir, 1948- (Abrahamic dialogues, 2007)
Contributing to the field of Islamic studies, philosophy and comparative religion to achieve a twofold objective, this work draws from various sources, especially in the domain of Sufism or Islamic mysticism. It is an in-depth meditation on the relationship between love and knowledge, mulitplicity and unity.